The Sustainability Cross Compliance of the Commodities Market in its Relationship with Derivative Financial Instruments - Leone, Maria; Manelli, Alberto; Pace, Roberta (Journal of Business Management and Economics, 2018)
Over the past decade, agricultural commodity prices underwent wild swings. Periods of high growth in 2008 were followed by periods of sudden decrease in 2009. The excessive increase in food price volatility is a subject of great interest because it has to do with the survival of mankind. Recent academic studies and policy makers have reached sharply different conclusions about the dynamics of such fluctuations. Also, some of them have indicated the main cause in speculative transactions and in the little regulation of futures markets. This paper analyzes weather agricultural price increases are due to increased speculative activity or to factors relating specifically to the commodities markets. The results of analysis do not show a direct relationship between the increase in speculative transactions and spot prices, rather a more developed future market can be of benefit also to spot prices, as argued in many academic studies.